Decrease in electrical contact resistance of Sb-doped n+-BaSi2 layers and spectral response of an Sb-doped n+-BaSi2/undoped BaSi2 structure for solar cells. (13th February 2018) - Kodama, Komomo; Takabe, Ryota; Yachi, Suguru; Toko, Kaoru; Suemasu, Takashi
Abstract: We investigated how the electron concentration n in a 300-nm-thick Sb-doped n + -BaSi2 layer grown by molecular beam epitaxy affected the contact resistance R C to surface electrodes (Al, indium–tin-oxide). As the n of n-BaSi2 increased, R C decreased and reached a minimum of 0.019 Ω cm 2 at n = 2.4 × 10 18 cm −3 for the Al electrodes. This value was more than 1 order of magnitude smaller than that obtained for Al/B-doped p-BaSi2 . We believe that this significant decrease in R C came from Sb segregation. Furthermore, the internal quantum efficiency ( IQE ) spectrum was evaluated for an Sb-doped n + -BaSi2 (20 nm)/undoped BaSi2 (500 nm)/n + -Si(111) structure. Its IQE reached as high as ∼50% over a wide wavelength range under a small bias voltage of 0.1 V applied between the top and bottom electrodes.